Neuronal Conditional Knockout of Collapsin Response Mediator Protein 2 Ameliorates Disease Severity in a Mouse Model of Multiple Sclerosis. (December 2019) - Moutal, Aubin; Kalinin, Sergey; Kowal, Kathy; Marangoni, Natalia; Dupree, Jeffrey; Lin, Shao Xia; Lis, Kinga; Lisi, Lucia; Hensley, Kenneth; Khanna, Rajesh; Feinstein, Douglas L.
We previously showed that treatment with lanthionine ketimine ethyl ester (LKE) reduced disease severity and axonal damage in an experimental autoimmune encephalomyelitis (EAE) mouse model of multiple sclerosis and increased neuronal maturation and survival in vitro . A major target of LKE is collapsin response mediator protein 2 (CRMP2), suggesting this protein may mediate LKE actions. We now show that conditional knockout of CRMP2 from neurons using a CamK2a promoter to drive Cre recombinase expression reduces disease severity in the myelin oligodendrocyte glycoprotein (MOG)35–55 EAE model, associated with decreased spinal cord axonal damage, and less glial activation in the cerebellum, but not the spinal cord. Immunohistochemical staining and quantitative polymerase chain reaction show CRMP2 depletion from descending motor neurons in the motor cortex, but not from spinal cord neurons, suggesting that the benefits of CRMP2 depletion on EAE may stem from effects on upper motor neurons. In addition, mice in which CRMP2 S522 phosphorylation was prevented by substitution for an alanine residue also showed reduced EAE severity. These results show that modification of CRMP2 expression and phosphorylation can influence the course of EAE and suggests that treatment with CRMP2 modulators such as LKE act in part by reducing CRMP2 S522 phosphorylation.